PEMEROLEHAN BAHASA SISWA TUNAGRAHITA KELAS VI SD - Reza Pandudinata; Sumarlam Sumarlam; Kundharu Saddhono (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
Abstract:  Language Acquisition of Mental Retardation Students at 6th Grade Elementary School. The aim of this research is to explain the comparison of vocabulary acquisition between student with severe mental retardation and student with mild mental retardation. This qulitative research used case study as strategy. Data collection technique used observation method and list of Swadesh Vocabulary. SLB YKK Pacitan was the location of this research. The result show that student with mild mental retardation can understand the vocabularies about 79%, and Nisa student with severe mental retardation can understand the vocabularies about 46%. This result proves that the ability of student with mild mental retardation to master vocabularies is better than the ability of student with severe mental retardation. Athough, the age of student with severe mental retardation is older than student with mild mental retardation. The mental age of the child with mental retardation influences their language ability.